2018
DOI: 10.1177/0733464818766666
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Stage and Social Support Mobilization for End-of-Life Caregivers

Abstract: Caregivers of terminally ill patients are at risk for anxiety, depression, and social isolation. Social support from friends, family members, neighbors, and health care professionals can potentially prevent or mitigate caregiver strain. While previous research documents the importance of social support in helping end-of-life caregivers cope with caregiving demands, little is known about differences in social support experiences among caregivers at different life course stages. Using life course theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Study results and research from within and outside of Taiwan all showed that most primary caregivers are family members that live with the patients. When the caregiver is the spouse, there is a responsibility to care for the family, and they are thus susceptible to more anxiety; due to long periods of caring for the patient, the caregiver can experience fatigue, insomnia, decrease in stamina, etc., and psychologically develop negative emotions such as frustration, sadness, anger, and depression [15,17,30,31,44].…”
Section: Lived With the Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study results and research from within and outside of Taiwan all showed that most primary caregivers are family members that live with the patients. When the caregiver is the spouse, there is a responsibility to care for the family, and they are thus susceptible to more anxiety; due to long periods of caring for the patient, the caregiver can experience fatigue, insomnia, decrease in stamina, etc., and psychologically develop negative emotions such as frustration, sadness, anger, and depression [15,17,30,31,44].…”
Section: Lived With the Patientsmentioning
confidence: 99%
“…Psychological and physical health impacts from the quality of care are very damaging to caregivers and care receivers. Research indicates that more help received from neighbors, professional medical personnel, or family and friends can reduce the stress on caregivers, demonstrating the importance of social support [17].…”
Section: Introductionmentioning
confidence: 99%